Mehrfache syntaktisch gleiche Nachfeldbesetzung und ihre Funktionen – Ergebnisse einer diachronen Analyse religiöser Texte - Ireneusz Gaworski (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
This article presents the results of a diachronic analysis of German Protestant funeral sermons which were published in the period from the mid-16th to the early 19th century. It analyses verb-final sentences in which more than one item with the same syntactic function appears in the Nachfeld field, i.e. to the right of the finite verb form. The aim was to examine (i) how this topological structure was manifested, (ii) which parts of the sentence occurred in it, (iii) how its development proceeded in the surveyed period (quantitative aspect), and (iv) what its purpose was.